Twenty‐year trends in patient referrals throughout the creation and development of a regional memory clinic network. Issue 1 (26th August 2020) - Chen, Yaohua; Lebouvier, Thibaud; Skrobala, Emilie; Volpe‐Gillot, Lisette; Huvent‐Grelle, Dominique; Jourdan, Nathalie; Leroy, Mélanie; Richard, Florence; Pasquier, Florence; ,
Abstract: Introduction: Memory clinics (MCs) are the main model for dementia diagnosis and care. Following the development of a MC network in Northern France, our objectives were to assess its impact on patient characteristics over 20 years. Methods: The characteristics of new consultants were studied from 1997 to 2016. Results: New consultants increased from 774 per year in 1997 to 26258 per year in 2016, as the number of MCs increased from 12 to 29. Over time, patients were progressively older and less educated, and more were living alone. A greater proportion of patients were referred by specialists. Referral delay and home‐to‐MC distance kept decreasing. The oldest patients were referred at a progressively less‐severe stage. The proportion of young patients kept increasing in the tertiary referral center. Discussions: The development of a region‐wide MC network led to increased referral of vulnerable patients and differentiation of the tertiary referral center over time.